Characteristics of microalgae spirulina biodiesel with the impact of n-butanol addition on a CI engine. (15th December 2019) - Rajak, Upendra; Nashine, Prerana; Verma, Tikendra Nath
Abstract: The aim of the present study is to investigate the effect of ternary blends of n-butanol-spirulina microalgae biodiesel and diesel fuel on compression ignition engine characteristics. Investigation was performed comparing n-butanol blended with microalgae spirulina biodiesel (MSB), low sulphur diesel and pure biodiesel at different engine loads. The MSB (40, 30 and 20%) – n butanol (10, 20 and 30%) blends were 50% with low sulphur diesel fuel in volume basis as B1 (LSD50-MSB40-nB10), B2 (LSD50-MSB30-nB20) and B3 (LSD50-MSB20-nB30). The comparison was made with diesel, biodiesel and n-butanol blended fuels which shows a reduction in exhaust gas temperature, Bosch smoke number (BSN), and brake specific particulate matter (BSPM) emission while showing higher specific fuel consumption (SFC), carbon dioxide, and nitrogen oxides emissions. The B20 blend led to a slight reduction in BTE (0.75%), NOX emission (12.58%), BSN (8.95%), and BSPM emission (31.88%) while increasing SFC as compared to diesel fuel. With the addition of the n-butanol in the diesel - microalgae spirulina biodiesel blends, brake thermal efficiency (BTE) has significantly improved during higher heat release rate and cylinder pressure while reduction in smoke and BSPM emissions at all engine loads for B1, B2 and B3 blends. Highlights: Comprehensive comparison of performance, combustion and emission characteristics of ternary fuel blends. Higher cylinder pressure, heat release and ignition delay values of n-butanol blends. Very close BTE values with to n-butanol blends. Significant reduction in smoke and PM emissions with the addition of n-butanol blends.